Effective antigen presentation to helper T cells by human eosinophils - Farhan, Ruhaifah K.; Vickers, Mark A.; Ghaemmaghami, Amir M.; Hall, Andrew M.; Barker, Robert N.; Walsh, Garry M. (Wiley, 2016)
Although eosinophils are inflammatory cells, there is increasing attention on their immunomodulatory roles. For example, murine eosinophils can present antigen to CD4+ T helper (Th) cells, but it remains unclear whether human eosinophils also have this ability. This study determined whether human eosinophils present a range of antigens, including allergens, to activate Th cells, and characterized their expression of MHC class II and co-stimulatory molecules required for effective presentation. Human peripheral blood eosinophils purified from non-allergic donors were pulsed with the antigens house dust mite extract (HDM), Timothy Grass extract (TG) or Mycobacterium tuberculosis purified protein derivative (PPD), before co-culture with autologous CD4+ Th cells. Proliferative and cytokine responses were measured, with eosinophil expression of HLA-DR/DP/DQ and the co-stimulatory molecules CD40, CD80 and CD86 determined by flow cytometry. Eosinophils pulsed with HDM, TG or PPD drove Th cell proliferation, with the response strength dependent on antigen concentration. The cytokine responses varied with donor and antigen, and were not biased towards any particular Th subset, often including combinations of pro- and anti-inflammatory cytokines. Eosinophils up-regulated surface expression of HLA-DR/DP/DQ, CD80, CD86 and CD40 in culture, increases that were sustained over 5 days when incubated with antigens, including HDM, or the major allergens it contains, Der p I or Der p II. Human eosinophils can, therefore, act as effective antigen-presenting cells to stimulate varied Th cell responses against a panel of antigens including HDM, TG or PPD, an ability that may help to determine the development of allergic disease.